Reconstruction of Islamic Banking Performance Measurement Models: A Critical Thought - Nur Maharani, Satia; Rahmawati, Setya Ayu; Syihhabudin, Syihhabudin; Gai Sin, Liem (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article presents critical thought related to the performance measurement of Islamic banks in terms of several perspectives, both legal, socio-cultural and expected measurement models. Performance assessment in conventional banks and sharia usually only are seen from the measurement of financial performance by using the CAMELS and RGEC ratios. Islamic banks in carrying out their duties must reevaluate the initial objectives. This is to ensure that they are not only profit-oriented. If the performance of Islamic and conventional banks is measured using the same indicators, there will be inappropriate values.